The prognosis of anti-angiogenesis treatments combined with standard therapy for newly diagnosed glioblastoma: a meta-analysis of randomized controlled trials - Li, Yuping; Hou, Mengzhuo; Lu, Guangyu; Ciccone, Natalia; Wang, Xingdong; Zhang, Hengzhu (PLOS ONE, 2016)
Background and Purpose Although bevacizumab (BV) has been approved as second-line therapy for recurrent glioblastoma (GB), the efficacy and safety of BV for patients with newly diagnosed GB remain unclear. Methodology/Principal Findings We systematically searched electronic databases (PubMed, EMBASE, OVID, etc.) to identify related studies published from January 1966 and August 2016. Eight randomized controlled trials including a total of 2,185 patients with GB were included. We found that the median progression-free survival (PFS) was higher in the BV group than in the standard therapy (ST) group (pooled hazard ratio, 0.73; 95%CI, 0.62-0.86; P = 0.0001). Compared with ST, BV improved the PFS rate at 6 months (OR 3.33, 95% CI 2.73-4.06, p<0.00001) and 12 months (OR 2.10, 95% CI 1.74-2.54, p<0.00001). There were no significant differences in median overall survival between the BV and ST groups (OR, 1.01; 95%CI, 0.83-1.23; P = 0.95). The BV group had higher survival rates at 6 months (OR, 1.41; 95% CI, 1.09-1.84; P = 0.01) and 12 months (OR, 1.23; 95% CI, 1.02-1.48; P = 0.03), but a low survival rate at the 36-month follow-up (OR, 0.57; 95% CI, 0.32-0.98; P = 0.04). For the incidence of adverse events, three adverse outcomes were found to be significantly different between BV and ST groups, including hypertension (8.37% vs. 1.62%, p<0.000001), proteinuria (7.65% vs. 0%, p<0.001), and fatigue (14.54% vs. 9.01%, p = 0.05). Conclusions/Significance Our study indicates that combination of BV with ST for newly diagnosed GB did not improve the median overall survival but result in longer median PFS, maintaining the quality of life and functional status. However, the long-term use of BV is associated with a higher incidence of adverse events and mortality. Study Registration This research was registered at PROSPERO. (Registration Number: CRD42016038247).